RESISTÊNCIA INSULÍNICA E RISCO CARDIOVASCULAR ASSOCIADOS ÀS DOENÇAS PERIODONTAIS EM ADOLESCENTES. - LADEIRA, Lorena Lúcia Costa (2018)
Introduction: Periodontal disease (PD) is again consistently associated with insulin resistance and cardiovascular and adult disease, when it is associated with progesterone syndrome. The cardiovascular risk in adolescents, using modeling of architectural equations. Method: Cross-sectional observational study carried out in São Luís, Maranhão, Brazil, in January 2014, July 2016. The random series is representative of students enrolled in the public network of São Luís, being applied in three stages: 1st stage - school; 2nd stage - class and 3rd stage - student. The date was formed by 405 adolescents of 17 and 18 years of age. Data were collected through a sociodemographic, nutritional (anthropometry), blood test, adipokine reading and dental examination questionnaire. The data were found to model equations as, with a latent variable construction based on the convergent factorial variables that form each latent variable in the exploratory factorial analysis (AFE). Later, they were validated by means of confirmatory factorial analysis (AFC), using software Mplus version 7.0. Results: Adolescents with greater extension of periodontal diseases have higher levels of resistance (PC = 0.152, p = 0.024) and triglycerides / HDL (CP = 0.141; p = 0.022). Conclusion: Topics of teaching models of the present study. The good constructs formed were able to secure some expected debts, although they continue to have a chance of error, with modeling analysis of non-study prospective equations. Levels more resistant to the disease and TG/HDL were denominated PD in adolescents, acting as responsible for the future risk to insulin resistance and cardiovascular diseases. These diseases and PDs have common metabolic risk parameters in the early stages of the life cycle.